Entry Modes and Liability of Foreignness Effects: Evidence From Russian Firms on the German Market - Panibratov, Andrei; Ribberink, Natalia; Nefedov, Konstantin (Organizations and Markets in Emerging Economies, 2018)
Foreign subsidiaries are at a disadvantage as compared to domestic enterprises, which is especially the case for emerging market firms in more developed economies. In this paper we apply liability of foreignness (LOF) concept to address the issue of these disadvantages. We consider LOF effects associated with equity vs. non-equity entry modes for Russian firms when penetrating the German market. The paper presents the results of a pilot study of 41 subsidiaries of Russian firms operating in different regions of Germany. Our results show that investors are more concerned about information, customers and partnerships, which can be explained by preeminent reliance on their own resources, while exporters appeared to be driven mostly by image considerations indicating minor interest in other characteristics of the host market. Although both exporters and investors experience significant negative effects from the lack of proper institutional and business knowledge on the host market, these effects vary for equity and non-equity entry modes. We suggest instruments to mitigate these effects, including cooperation with institutional agents, which is especially important for FDI strategy.